Assessment of the Tertiary Irrigation System in Bulutimorang Irrigation Area, Sidrap Regency - Ridha Izzulhaq, Muhammad; Iqbal; Mahmud Achmad; Fadhil Surur; Husnul Mubarak (Salaga Journal, 2024)
Irrigation plays a crucial role in agriculture, particularly in Indonesia, by ensuring a stable water supply for rice fields, thereby enhancing crop productivity and optimizing water use. The efficiency of an irrigation network directly impacts water distribution, making it essential to assess system performance regularly. This study evaluates the performance of the tertiary irrigation system in the Bulutimorang Irrigation Area, Sidrap Regency, and maps the condition of its existing physical infrastructure. The research was conducted from May to July 2023 and involved field surveys, network tracing, and interviews with farmers, sluice gate officers, and irrigation personnel (juru/mantri). Data were analyzed to validate key performance indicators based on the Regulation of the Minister of PUPR No. 12/PRT/M/2015. The results indicate that the tertiary irrigation network in the Bulutimorang Irrigation Area is functioning well, with an overall performance score of 72.06%. These findings highlight the need for continued maintenance and improvement strategies to sustain efficient irrigation management in the region.